Thermodynamic and mathematical analysis of geothermal power plants operating in different climatic conditions - Basaran, Tugrul; Cetin, Burhanettin; Ozdemir, Mehmed Rafet (ELSEVIER, 2022)
This study presents the thermodynamic and mathematical analysis of the different cooling systems for geothermal power plants at various climatic conditions. The existing binary geothermal power plant data, located in Turkey, were processed in the commercial software Ebsilon Professional to model the power plant and cooling systems. The dry-bulb temperature and relative humidity values from data obtained from local meteorological stations in the analyzed region are used as variables in the model. The reference air-cooled cooling system, the wet-tower cooling system, the additional dry cooling system and three different hybrid cooling systems are modelled and analyzed separately in the reference geothermal power plant model. Accordingly, mathematical equations are developed to evaluate the power production and water consumption characteristics of cooling systems on the thermodynamic performance of geothermal power plants depending on weather conditions. The power production and water consumption of geothermal power plants can be calculated using hourly ambient temperature and relative humidity data at different climatic conditions with these equations. Considering water reserves in the area, operation periods of the hybrid cooling systems can be determined. Moreover, power plant operators can compare the performance and water consumption characteristics of hybrid cooling systems for different conditions with these equations.
Keywords: Geothermal power plants; Hybrid cooling systems; Mathematical modelling; Thermodynamic analysis; ENERGY; Thermodynamics